Chaos Theory: A New Science for Sport Behavior? - Mack, M. G.; Huddleston, S.; Dutler, K. E.; Mintah, J. K. (Athletic Insight - The Online Journal of Sport Psychology, 2000)
Current theoretical approaches to research have contributed to our understanding of the effect of selected variables on other variables, yet have not sufficiently moved the sport psychology field closer to the goal of understanding, explaining, and predicting complex sport behavior. Therefore, the purpose of this paper is to present a brief overview of a more macroscopic approach for studying the complex, nonlinear system of sport behavior, namely chaos theory. Chaos based research may yield patterns of behavior which may provide a more functional understanding of sport behavior.